Imagens da prostituição feminina - Schouten, Maria Johanna Christina (2018)
Esta abordagem do fenómeno de prostituição feminina foca o impacto da imagem negativa de trabalhadoras sexuais na sua auto-imagem e no seu estatuto na sociedade. Neste contexto, discute-se noções de estigma (Goffman) e opiniões divergentes sobre a comodificação da sexualidade, com referência a autores como Simmel e Appadurai. Ilustrações são apresentadas das atitudes face a trabalhadoras sexuais em vários países e em vários períodos, em particular na história de Portugal. This approach to the phenomenon of female prostitution focuses on the impact the negative image of sex workers has on their own self-image and on their status in society. In this context, notions about stigma (Goffman) are examined and divergent opinions about the commodification of sexuality, drawing on authors such as Simmel and Appadurai, are discussed. Illustrations are provided of the attitudes towards female sex workers in various countries, and in various periods, in particular in the history of Portugal.